2018
DOI: 10.1097/dcr.0000000000001013
|View full text |Cite
|
Sign up to set email alerts
|

The Price We Pay for Radical Curative Pelvic Exenterations: Prevalence and Management of Pain

Abstract: Perioperative pain is a significant issue among patients undergoing pelvic exenteration. One in three patients require high-dose opiates preoperatively that is associated with worse pain outcomes. Potential areas to improve pain outcomes in these complex patients could include increased use of regional anesthesia, antineuropathic agents, and opiate-sparing techniques. See Video Abstract at http://links.lww.com/DCR/A572.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…L5 and S1 are required for acceptable motor function and avoidance of an ipsilateral foot drop. Postoperative pain is also a significant problem for patients undergoing sacrectomy, with a subsequent impact on quality of life, irrespective of the sacrectomy level [ 42 , 43 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…L5 and S1 are required for acceptable motor function and avoidance of an ipsilateral foot drop. Postoperative pain is also a significant problem for patients undergoing sacrectomy, with a subsequent impact on quality of life, irrespective of the sacrectomy level [ 42 , 43 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Ten studies (47%) were judged to be at moderate risk of bias [2–5, 21, 26, 29, 30, 32, 35]. Another 10 studies (47%) were at serious risk of bias [19, 20, 22–24, 27, 28, 31, 33, 34]. One study, which was a conference abstract, was considered to have a critical risk of bias [25].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of reported pain outcomes is presented in Table 2. Pain outcomes were reported using the Verbal Numerical Rating Scale (VNRS; n = 2 studies) [26, 28], Visual Analogue Scale (VAS; n = 1 study) [26], 36‐item Short Form Survey (SF‐36; n = 3 studies) [3, 21, 24], Brief Pain Inventory (BPI; n = 2 studies) [4, 20], European Organisation for the Research and Treatment of Cancer – Quality of Life Questionnaire (EORTC QLQ; n = 4 studies) [29, 30, 32, 35] Psychological Distress Inventory (PDI) and Mini‐Mental Adjustment to Cancer (Mini‐MAC; n = 1 study) [26] measures.…”
Section: Resultsmentioning
confidence: 99%
“…18,77 The themes identified were symptoms, sexual function, psychological impact, role and social functioning, future perspective and healthcare service utilisation and delivery. Nineteen (54.3%) of the studies identified in this review have been published since this work, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] using a median of two PROMS, with the EORTC QLQ-CR29 and FACT-C most used. The EORTC QLQ-CR29 and FACT-C have also both demonstrated robust psychometric properties, including content validity, in patients with primary colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%